LEGAL ANALYSIS OF THE GRANTING OF OWNERSHIP RIGHTS TO APARTMENT UNITS FOR FOREIGN CITIZENS IN GOVERNMENT REGULATION NUMBER 18 OF 2021 CONCERNING MANAGEMENT RIGHTS, LAND RIGHTS, APARTMENT UNITS AND LAND REGISTRATION REVIEWED FROM THE PRINCIPLES OF THE MATE - Mayangsari, Devi Meilisa (AKSELERASI: Jurnal Ilmiah Nasional, 2024)
Granting ownership rights to apartment units for Foreign Citizens is one of the efforts to increase investment and the national economy. The establishment of harmonious and integrated laws and regulations is needed to develop laws and regulations that support national development in general. This journal will discuss four key principles: legal certainty, harmony, compatibility, and justice. While these principles may not be explicitly stated, they are acknowledged and implemented in state administrative practices. Nevertheless, granting these rights introduces various legal challenges, particularly regarding the ownership of land and buildings, including apartment units by foreign nationals in Indonesia, which must comply with Indonesian national law based on the nationality principle. It should be remembered that land and buildings/apartments on it are separate rights because the UUPA adopts the principle of horizontal separation. Therefore, buildings/apartments located on the land are no longer a single unit of the land so ownership of the building/apartment is not the property of the landowner. Granting ownership rights to apartments to foreign nationals, automatically reduces the welfare of the people in obtaining a place to live. By granting an increase in the status of rights to foreign nationals over flats, it also results in a conflict with the previously regulated legal regulations contained in the UUPA regarding the status of rights granted to foreign nationals only as usage rights, so it is feared that it will cause legal uncertainty. Regarding the implementation of the principles of the contents of the laws and regulations in the provisions on granting ownership rights to flats for Foreign Citizens contained in Government Regulation Number 18 of 2021, one of which is to overcome this legal problem, there needs to be provisions that limit the granting of ownership rights to flats to foreign nationals.